Spiral dynamics in action : humanity's master code - Beck, Don (Don Edward) (John Wiley & Sons, 2018)
A more effective leadership model for the new business environment. Spiral Dynamics in Action explores the evolution of modern business, and provides a model for moving forward amidst ever-increasing complexity and change. Only by truly understanding other people's perspectives can you bring them together to achieve the extraordinary, and this book provides a field guide to the different motivations, behaviours and talents in your team to help you lead diverse groups more effectively. Focused on action over theory, the Spiral Dynamics model includes cutting-edge leadership practices, management systems, processes, procedures and techniques to help you bring about real-world results. The nature of change is consistent, but that doesn't make it any less enormous or complex to deal with. As a business leader, you are tasked with not only navigating change yourself, but also guiding others through the maze successfully. This book shows you how to shift your perspective, hone your focus and deliver what your people need by: -Understanding the reasoning behind different perspectives. -Helping people play off one another's strengths to achieve a shared goal. -Adopting cutting-edge practices, processes and procedures for improvement. -Taking action to re-connect an increasingly fragmented environment. The marketplace has gone truly global, workforces are increasingly diverse and companies are taking on powerful new social responsibilities. It's a lot to take in, let alone manage, but the responsibility of leadership is to gather disparate parts and make them into a whole. It's your job to turn anchors into rocket fuel, and motivate and inspire your team to the top. By digging to the core of each person, each culture and each problem, you uncover a roadmap to high performance; Spiral Dynamics in Action shows you how to guide your people through any changes and emerge stronger than before.